2020
DOI: 10.3390/nano10040815
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Cellular Uptake and Antibacterial Activity of Rifampicin through Encapsulation in Mesoporous Silica Nanoparticles

Abstract: An urgent demand exists for the development of novel delivery systems that efficiently transport antibacterial agents across cellular membranes for the eradication of intracellular pathogens. In this study, the clinically relevant poorly water-soluble antibiotic, rifampicin, was confined within mesoporous silica nanoparticles (MSN) to investigate their ability to serve as an efficacious nanocarrier system against small colony variants of Staphylococcus aureus (SCV S. aureus) hosted within Caco-2 cells. The sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 65 publications
2
21
0
Order By: Relevance
“…Importantly, this effect does not seem to be dose-dependent, and could be attributed to mechanical obstruction of the materials to cell proliferation potential [ 34 , 35 ]. The results obtained in the current study are in good agreement with previous studies where ordered mesoporous silica did not exhibit any toxicity when tested in Caco-2 cell lines [ 36 , 37 , 38 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Importantly, this effect does not seem to be dose-dependent, and could be attributed to mechanical obstruction of the materials to cell proliferation potential [ 34 , 35 ]. The results obtained in the current study are in good agreement with previous studies where ordered mesoporous silica did not exhibit any toxicity when tested in Caco-2 cell lines [ 36 , 37 , 38 ].…”
Section: Resultssupporting
confidence: 92%
“…Finally, the cell viability study of Caco-2 cells incubated with MCM-41 and MCM-48 in the presence and absence of aprepitant showed that both materials do not present any significant toxicity in vitro, in good agreement with previously reported studies on similar materials [ 36 , 37 , 38 ]. All above results confirm that ordered mesoporous silica nanoparticles such as MCM-41 and MCM-48 provide a good platform for the development of effective aprepitant carriers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among the class of inorganic nanomaterials mesoporous silica nanoparticles (MSN) are a promising drug delivery system for small molecule as well as protein/peptide and DNA/RNA based drugs. [21][22][23] The most outstanding properties of this class of material relevant for the application as a drug vector include the tunability in particle size, morphology and charge, various geometries and dimensions of the porous network and in most cases high biocompatibility and tunable biodegradability. Several studies underline that MSN have a great potential as drug delivery system in tuberculosis therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In another interesting set of contributions, Subramaniam et al and Joyce et al evaluated the behavior between MSNs with different particle sizes 41 and surface functionalization 42 to be tested on S. aureus intracellular infections. In these contributions the authors employed Hiroshima mesoporous materials (HMM) with sizes in the range of 40–100 nm and rifampicin as antibiotic cargo.…”
Section: Delivery Of Antibiotic Compoundsmentioning
confidence: 99%